Analisa Kebutuhan dan Preferensi Pengguna Kantin Auditorium Universitas Negeri Medan: INDONESIA - Khairuni, Zhilli Izzadati; Trimailuzi, Trimailuzi; Arini, Nur; Nabila, Alya Nur; Fadilah, Alya Rizky; Sitio, Desfi Mayshinta; Hutagalung, Kisrani; Dika, Ewin Avriza; Azrun, Riyadh Riyadhi (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
The campus canteen has an important role in supporting students' academic and social activities. The architectural design of the canteen that considers the comfort and needs of the user is crucial. This study aims to analyze the facilities and design of the canteen of the State University Auditorium of Medan State University in order to improve the quality of service and aesthetics based on user preferences. The methods used are descriptive qualitative, including literature studies, field observations, and user satisfaction surveys. The results of the analysis show that most users stated that there is a need to improve the layout, material selection, and visual concept to create a comfortable, functional, and attractive canteen for the campus academic community and the public.